The Factors Analysis of Financial Conditions of Working Women Sandwich Generation - Sayu Ketut Sutrisna Dewi; I Gusti Bagus Wiksuana (Signifikan: Jurnal Ilmu Ekonomi, 2022)
Balinese women are known as primary caregivers and breadwinners for their families, strength, and involvement in various community activities. The purpose of this study was to examine the factors that influence financial conditions and the role of financial literacy in mediating the relationship between factors that affect financial conditions. This research is descriptive-quantitative research using SEM-PLS analysis. The findings reveal that culture, social support, and financial literacy simultaneously positively impact financial conditions. From this research, it is also known that financial literacy acts as a mediator between the influence of culture and social support on financial conditions and also the influence of financial literacy on financial conditions. Therefore, financial literacy is very important to avoid financial pressure. Moreover, for the women of the sandwich generation to perform well while dealing with financial stress, social support is needed.How to Cite:Dewi, S. K. S., & Wiksuana, I. G. B. (2022). The Factors Analysis of Financial Conditions of Working Women Sandwich Generation. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 299-318. https://doi.org/10.15408/sjie.v11i2.25635.JEL Classification: M14, L31, F36, G530